2010
DOI: 10.1080/10454431003736227
|View full text |Cite
|
Sign up to set email alerts
|

How Apparent Digestibility of Carotenoids, Macronutrients, and Minerals are Differently Affected by Ration Level in Atlantic Salmon,Salmo Salar

Abstract: The main objective of this field experiment was to investigate whether ration level affected utilization of carotenoids, macronutrients, and minerals in 1,300 g Atlantic salmon (Salmo salar) during rapid growth. Salmon fed ration levels of either 1.2% or 0.6% of biomass of a commercial diet supplemented with astaxanthin and canthaxanthin (37 and 39 mg kg −1 , respectively) in two consecutive 6-day feeding periods had carotenoid digestibility coefficients of 11.8% and 32.1% at the high and low feed rations, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…; Rørvik et al . ). However, the slightly higher growth rate of the salmon fed the krill diet was not enough to cause significant differences in fillet colour or texture compared with the control diet.…”
Section: Discussionmentioning
confidence: 97%
“…; Rørvik et al . ). However, the slightly higher growth rate of the salmon fed the krill diet was not enough to cause significant differences in fillet colour or texture compared with the control diet.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, free AST is usually absorbed and deposited better than AST ester [43]. The latter needs to be hydrolysed into free form, incorporated into mixed micelles or lipoproteins, absorbed in the intestine and finally transported to the liver and deposited in muscle [44]. Intestinal hydrolysis or cleavage could be a limiting step for the absorption of AST from its ester matrix [39].…”
Section: Discussionmentioning
confidence: 99%
“…The colour drop seen during autumn is concurrent with shorter days in both smolt groups, but the reason for this is unknown. A recently published study has shown reduced carotenoid digestibility with increased feed rations, possible explaining poorer pigmentation in rapidly growing salmon (Rørvik et al 2010). Reduced meal frequency had a temporal negative effect on colour, probably due to temporal reduced feed provision (affecting feed intake) and hence lower intake of pigments.…”
Section: Aquaculture Nutritionmentioning
confidence: 99%